Occurrence of plastic particles in procellariiforms, south of São Paulo state (Brazil) - Barbieri,Edison (2009)
Seabirds ingest plastic particles floating on the surface of the world's oceans. The birds can ingest plastic particles that they mistakenly identify as prey items. Alternatively, plastics can be taken up in the stomach contents of prey species. Plastic is often passed from parents to chicks in regurgitated food. In this study, individual petrels and albatrosses brought in by the tide onto Ilha Comprida beach between January 2000 and December 2002 were collected. Ilha Comprida, a barrier island in southern São Paulo, Brazil, was traversed by car along a transect of 70 kilometers. A total of 110 birds of 10 species were collected and 64.54% had plastic particles in their stomach. Frequencies of occurrence were Macronectes giganteus (64.28%), Thalassarche melanophrys (73.07%), Thalassarche chlororhinchos (44.44%), Puffinus puffinus (85.71%), Puffinus gravis (7.41%), Puffinus griseus (63.63%), Fumarus glacialoides (33.33%), Daption capensis (75%), Pachyptila belcheri (33.33%), Procellaria aequinoctialis (25%). These results demonstrated the extent of contamination with plastic and the possible harmful effects on seabirds.